Laser protection multi-layer composite structure applied to unmanned aerial vehicle and preparation method of laser protection multi-layer composite structure
Through the design of multi-layer composite structural coating, using specific material combination and spin coating, the problems of thermal damage, high cost and poor anti-laser performance of the drone laser protective coating under high-energy laser radiation are solved, achieving high efficiency Improved laser protection and mechanical properties.
Patent Information
- Application Number
- CN202411577602.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-01-14
AI Technical Summary
The existing drone laser protective coatings have problems such as thermal damage, high cost, poor anti-laser radiation performance and insufficient mechanical properties under high-energy laser radiation radiation, and the thermal spraying method is not conducive to lightweight composite drones.
Designed with multi-layer composite structural coating, including cracking absorption layer, thermal evacuation layer, heat insulation layer and reflective absorbing layer, it is prepared by spin coating method, using TiO2, B4C, SiC, graphene, Ag/Cu, ZrO2, Mo , Y2O3, Al, ZrO2, Fe3O4, cBN and other materials realize reflection, insulation, thermal conductivity and absorption of laser energy, and improve the mechanical properties and stealth properties of the coating.
Effectively protect the drone from high-power laser ablation, extends the coating life, reduces preparation costs, improves anti-laser performance and mechanical properties, and is suitable for lightweight composite material drones.
Smart Images

Figure CN119309457A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of unmanned aerial vehicle laser protection, and in particular relates to a laser protection multi-layer composite structure applied to unmanned aerial vehicles and a preparation method thereof. Background Art
[0002] The main form of damage to drones caused by high-energy laser weapons is the thermal damage to materials caused by highly localized laser energy. Therefore, based on the attack nature of laser weapons, to achieve drone protection against laser weapons, the high-energy laser beams emitted by laser weapons should first be prevented from coming into contact with drones to achieve physical isolation. Based on the structural and functional characteristics of drones, coating technology is the most effective way to protect against lasers.
[0003] The Chinese invention patent with publication number CN109536870A discloses a laser protective coating and its preparation method. The coating includes a Ni / Al layer, an Al2O3 layer, an Al / Al2O3 composite layer and an Al layer stacked in sequence, wherein the Ni / Al layer is made of nickel-coated aluminum powder, and the Al / Al2O3 composite layer is made of a mixed powder of Al and Al2O3. The coating does not contain impurities and is highly consistent with the designed composition. The coating is tightly bonded to the substrate interface and has a high bonding strength of up to 12MPa. The coating can effectively resist 1kW / cm 2 After 30 seconds of laser irradiation, the coating remained intact with only slight ablation, and the coating had no defects such as cracking, warping or peeling. However, the coating disclosed in the patent can only rely on Al to reflect part of the laser energy, and most of the heat generated by the energy is still transferred to the substrate, and the heat insulation effect of Al2O3 can only withstand about 30 seconds of laser irradiation.
[0004] The Chinese invention patent with publication number CN111996531A discloses a laser protective coating and a preparation method thereof, wherein the laser protective coating comprises a zinc-immersion layer, a Ni / nA l2 O3 electroplating layer and Ni / n-Al2O3 spraying layer, the Ni / n-Al2O3 electroplating layer includes nickel and nano-alumina (n-Al2O3); the Ni / n-Al2O3 spraying layer includes nano-alumina (n-Al2O3) powder and nickel powder and / or nickel alloy powder. The coating of the present invention has strong bonding force with the substrate, low internal stress, is not prone to cracking, peeling and other problems, and has excellent laser protection ability, which can withstand 1kW / cm 2 Laser 10s, 600w / cm 2After 100s of laser irradiation, the coating surface only slightly burns, and only partially melts under irradiation of 2-5 times the above energy laser, without burning, breakdown, cracking, peeling, etc. The electroplating method used in the coating preparation method disclosed in the patent consumes a lot of energy, and the three different coatings use different preparation processes, which are cumbersome and complicated.
[0005] The Chinese invention patent with publication number CN112779535A discloses a laser-resistant coating for the surface of a substrate and a preparation method thereof. A molybdenum zirconium oxide thermal insulation layer is prepared on the surface of an aluminum alloy by supersonic plasma spraying technology, a gradient zirconium oxide aluminum transition layer is prepared by supersonic plasma spraying coupled with cold spraying, and then an aluminum graphene reflective layer is prepared by cold spraying technology. The prepared laser-resistant coating has a controllable thickness, high coating bonding strength, low porosity, good thermal insulation performance and reflectivity, and can resist high-power density laser ablation. In addition, the preparation method of the present invention has the characteristics of simple, convenient and flexible operation, stable process, and controllable process, and has good application prospects. However, the preparation of the coating by supersonic plasma spraying has a large heat input to the substrate, which can easily cause the substrate to deform due to heat, and is not suitable for equipment such as drones that have precision electronic devices inside.
[0006] Therefore, the existing laser protection layer structure has the following technologies when applied to UAVs
[0007] question:
[0008] 1. Most of the methods used in the patents and papers that have been published so far are to prepare laser ablation-resistant coatings on the substrate surface by thermal spraying. However, most drones use lightweight composite thin-walled materials such as carbon fiber. If thermal spraying is used, the thermal damage to the key components of the drone is large, and the preparation cost is high, which is not conducive to the mass production of drone protective coatings.
[0009] 2. Most anti-laser ablation coatings have poor resistance to laser radiation and only resist laser ablation through heat insulation, which cannot provide good protection for drones.
[0010] 3. A single laser energy absorption layer cannot meet the requirements of existing UAV working conditions. The mechanical properties, wear resistance and stealth performance of the anti-laser ablation coating in the currently disclosed patents are relatively poor. Summary of the invention
[0011] The present invention aims to solve at least one of the technical problems existing in the prior art and provide a new technical solution for a laser protection multi-layer composite structure applied to unmanned aerial vehicles and a manufacturing method thereof.
[0012] According to a first aspect of the present invention, there is provided a laser protection multilayer composite structure for use in an unmanned aerial vehicle, comprising:
[0013] A cracking absorption layer, the cracking absorption layer covers the surface of the substrate; the cracking absorption layer comprises TiO2, B4C, SiC particles and polysilazane, and the mass ratio of TiO2, B4C, SiC particles is (2-7): (5-8): (5-10), and the total mass percentage is 15%-25%;
[0014] A heat dissipation layer, the heat dissipation layer covers the surface of the cracking absorption layer; the heat dissipation layer comprises graphene, Ag / Cu and silicone resin, and the mass ratio of graphene to Ag / Cu is (5-10):(5-10), and the total mass percentage is 10%-20%;
[0015] A heat-insulating layer, the heat-insulating layer covering the surface of the heat-dissipating layer; the heat-insulating layer comprises ZrO2, Mo, Y2O3 and polysilazane, and the mass ratio of ZrO2, Mo and Y2O3 is (5-10):(3-7):(4-8), and the total mass percentage is 18%-25%;
[0016] A reflective absorbing layer, which covers the surface of the thermal insulation layer; the reflective absorbing layer comprises Al, ZrO2, Fe3O4, cBN and silicone resin, and the mass ratio of Al, ZrO2, Fe3O4 and cBN is (5-10):(5-10):(3-5):(3-5), and the total mass percentage is 20%-30%.
[0017] According to a second aspect of the present invention, there is provided a method for preparing a laser protection multilayer composite structure for use in an unmanned aerial vehicle, comprising the following steps:
[0018] Step S100, pre-treating the substrate;
[0019] Step S200, preparing a cracking absorption layer, comprising:
[0020] Step S201, preparing a precursor solution; wherein the precursor solution comprises polysilazane and a diluent; the diluent is n-butanol, or acetone, or ethylene dichloride, or ethanol;
[0021] Step S202, adding TiO2, B4C, and SiC particles to the precursor solution in sequence, stirring evenly, placing the mixture in an ultrasonic disperser for ultrasonic dispersion for 5-10 minutes, and then adding a defoamer with a mass fraction of 0.4%-0.8%, and continuing to stir in an electromagnetic stirrer for 10-15 minutes to form a first mixed solution; wherein, in the first mixed solution, the mass ratio of TiO2, B4C, and SiC particles is 2-7:5-8:5-10, and the total mass percentage is 15%-25%;
[0022] Step S203, coating the pretreated substrate with the first mixed solution by spin coating, and curing in an Ar atmosphere to form a cracking absorption layer on the surface of the substrate;
[0023] Step S300, preparing a heat dissipation layer, comprising:
[0024] Step S301, preparing an organic resin mixed solution; wherein the organic resin mixed solution comprises an organic silicon resin and a solvent; the solvent is acetone, ethanol, or xylene;
[0025] Step S302, adding graphene, Cu or Ag particles to the organic resin mixed solution in sequence, stirring evenly, placing it in an ultrasonic disperser for ultrasonic dispersion for 3-5 minutes, and then adding a defoamer with a mass fraction of 0.3%-0.5%, and continuing to stir in an electromagnetic stirrer for 8-10 minutes to form a second mixed solution; wherein, in the second mixed solution, the mass ratio of graphene to Ag / Cu is 5-10:5-10, and the total mass percentage is 10%-20%;
[0026] Step S303, coating the heat dissipation layer with the second mixed solution by spin coating, and curing in an Ar atmosphere to form a heat dissipation layer on the surface of the cracking absorption layer;
[0027] Step S400, preparing a heat insulation layer, includes:
[0028] Step S401, preparing a precursor solution; wherein the precursor solution comprises polysilazane and a diluent; the diluent is n-butanol, or acetone, or ethylene dichloride, or ethanol;
[0029] Step S402, adding ZrO2, Mo, and Y2O3 particles to the precursor solution in sequence, stirring evenly, placing the mixture in an ultrasonic disperser for ultrasonic dispersion for 8-12 minutes, and then adding a defoamer with a mass fraction of 0.4%-0.7%, and continuing to stir in an electromagnetic stirrer for 10-15 minutes to form a third mixed solution; wherein, in the third mixed solution, the mass ratio of ZrO2, Mo, and Y2O3 is 5-10:3-7:4-8, and the total mass percentage is 18%-25%;
[0030] Step S403, coating the heat insulation layer with the third mixed solution by spin coating, and curing in an Ar atmosphere to form a heat insulation layer on the surface of the heat dissipation layer;
[0031] Step S500, preparing a reflective absorbing layer, includes:
[0032] Step S501, preparing an organic resin mixed solution; wherein the organic resin mixed solution comprises an organic silicon resin and a diluent; the diluent is acetone, or ethanol, or ethylene dichloride;
[0033] Step S502, Al, ZrO2, Fe3O4, cBN particles are added to the organic resin mixed solution in sequence, stirred evenly, and then placed in an ultrasonic disperser for ultrasonic dispersion for 8-12 minutes, and then a defoamer with a mass fraction of 0.4%-0.7% is added, and the mixture is stirred in an electromagnetic stirrer for 9-12 minutes to form a fourth mixed solution; wherein, in the fourth mixed solution, the mass ratio of Al, ZrO2, Fe3O4, and cBN is 5-10:5-10:3-5:3-5, and the total mass percentage is 20%-30%;
[0034] Step S503 , coating the reflective absorbing layer with the fourth mixed solution by spin coating, and curing the mixed solution in an Ar atmosphere to form a reflective absorbing layer on the surface of the heat insulation layer.
[0035] Optionally, the substrate is pretreated, including:
[0036] The substrate surface and edges were smoothed with sandpaper and then ultrasonically cleaned in acetone.
[0037] Optionally, the material of the substrate is a carbon composite material; the sandpaper is 100-mesh sandpaper; the temperature of ultrasonic cleaning is 25° C., and the cleaning time is 5 min.
[0038] Optionally, preparing a precursor solution comprises:
[0039] Dissolve polysilazane in n-butanol, or acetone, or ethylene dichloride, or ethanol to obtain a precursor solution, and stir it with an electric stirrer for 3-6 minutes; wherein the mass fraction of polysilazane in the precursor solution is 55-65%.
[0040] Optionally, preparing a mixed solution of an organic silicone resin comprises:
[0041] The organic silicon resin is dissolved in acetone, ethanol or dichloroethane to obtain an organic resin mixed solution, and an electric stirrer is used to stir the solution for 2-3 minutes; wherein the mass fraction of the organic silicon resin in the organic resin mixed solution is 50-60%.
[0042] Optionally, in step S202, after TiO2, B4C, and SiC particles are sequentially added to the precursor solution, the precursor solution is stirred with an electric stirrer for 5-7 minutes;
[0043] And / or, in step 402, after ZrO2, Mo, and Y2O3 particles are added to the precursor solution in sequence, the precursor solution is stirred with an electric stirrer for 5-7 minutes.
[0044] Optionally, in step S302, after graphene, Cu or Ag particles are sequentially added to the organic silicone resin mixed solution, an electric stirrer is used to stir the organic resin mixed solution for 3-5 minutes;
[0045] And / or, in step 502, after Al, ZrO2, Fe3O4, and cBN particles are sequentially added to the organic silicon resin mixed solution, the precursor solution is stirred with an electric stirrer for 3-5 minutes.
[0046] Optionally, in step S202, the particle sizes of TiO2, B4C, and SiC particles are 300nm-700nm respectively;
[0047] and / or, in step 302, the particle sizes of graphene, Cu or Ag are 500 nm-1000 nm respectively;
[0048] And / or, in step 402, the particle sizes of ZrO2, Mo, and Y2O3 particles are 500nm-800nm respectively.
[0049] And / or, in step 502, the particle sizes of Al, ZrO2, Fe3O4, and cBN particles are 600nm-1000nm respectively.
[0050] Optionally, when the coating is performed by spin coating, the rotation speed is 1600 r / min-2000 r / min, and the time is 30 s-60 s.
[0051] Optionally, when curing is performed in an Ar atmosphere, the curing conditions are as follows:
[0052] The temperature was first raised to 230°C at a heating rate of 2°C / min and kept at this temperature for 2h, and then cooled to 25°C at a cooling rate of 5°C / min and kept at this temperature for 0.5h.
[0053] Optionally, the cracking absorption layer, the heat dissipation layer, the heat insulation layer, and the reflective absorbing layer all have a thickness of 200 μm-400 μm.
[0054] A technical effect of the present invention is:
[0055] In the embodiment of the present application, the pyrolysis absorption layer is covered on the surface of the substrate by spin coating, and the heat dissipation layer is covered on the surface of the pyrolysis absorption layer, and the heat insulation layer is covered on the surface of the heat dissipation layer, and the reflective wave absorbing layer is covered on the surface of the heat insulation layer. Among them, the reflective wave absorbing layer has the effect of reflecting and absorbing waves, the heat insulation layer has the effect of heat insulation, the heat dissipation layer has the effect of heat conduction and heat equalization, and the pyrolysis absorption layer has the effect of absorbing and consuming laser energy and generating high-temperature ceramics, so that each coating of the substrate can achieve the purpose of reflecting and absorbing waves, heat insulation, heat conduction and heat equalization, and absorbing and consuming energy from top to bottom in sequence;
[0056] Furthermore, the reflective absorbing layer, as a surface layer capable of reflecting laser light, reflects part of the laser light by doping with aluminum powder; after laser irradiation, ZrO2 undergoes a phase change, consuming part of the energy, and at the same time, causing the emissivity of the coating to increase, further reducing the irradiation energy of the laser; nano-cBN compensates for phase defects in the coating, improves the mechanical properties of the reflective absorbing layer, and prolongs the service life of the coating. In addition, the doped Fe3O4 particles can absorb radar waves, allowing the drone to avoid radar tracking to a certain extent.
[0057] The thermal insulation layer is an intermediate coating that can isolate heat transfer. It uses the cracking of polysilazane to absorb part of the laser energy and heat to generate SiCN ceramics with high-temperature thermal insulation. ZrO2, Mo, and Y2O3 particles have the characteristics of low thermal conductivity and high temperature resistance, which prevent heat from being transferred to the inside of the coating.
[0058] As an intermediate layer coating that can quickly conduct heat to avoid heat accumulation, the heat dissipation layer uses the delayed effect of the thermal insulation layer to block heat transfer, and uses the strong thermal conductivity of graphene, Cu or Ag to quickly transfer heat laterally to increase the heated area, thereby avoiding damage to the coating caused by heat accumulation.
[0059] The cracking absorption layer serves as a bottom coating that can absorb and consume heat. It uses polysilazane to absorb laser energy and interacts with SiC to crack and produce a large amount of SiCN ceramics, which consumes the energy inside the coating. At the same time, it cooperates with the high-temperature resistant TiB2 and TiC converted from TiO2 and B4C to hinder the transfer of heat, thereby protecting the drone. BRIEF DESCRIPTION OF THE DRAWINGS
[0060] Figure 1 This is a schematic structural diagram of a laser protection multi-layer composite structure applied to a drone according to an embodiment of the present invention;
[0061] Figure 2 The present invention is a flowchart of a method for manufacturing a laser protection multi-layer composite structure applied to an unmanned aerial vehicle according to another embodiment of the present invention.
[0062] In the figure: 1. substrate; 2. cracking absorption layer; 3. heat dissipation layer; 4. thermal insulation layer; 5. reflection absorbing layer. DETAILED DESCRIPTION
[0063] Various exemplary embodiments of the present application will now be described in detail with reference to the accompanying drawings. It should be noted that unless otherwise specifically stated, the relative arrangement of components and steps, numerical expressions and numerical values set forth in these embodiments do not limit the scope of the present application.
[0064] The embodiments of the present application will be described in detail below, and examples of the embodiments are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present application, and should not be construed as limitations on the present application. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present application.
[0065] According to a first aspect of the present invention, see Figure 1 , provides a laser protection multi-layer composite structure for unmanned aerial vehicles, including:
[0066] A cracking absorption layer 2, the cracking absorption layer 2 covers the surface of the substrate 1; the cracking absorption layer 2 comprises TiO2, B4C, SiC particles and polysilazane, and the mass ratio of TiO2, B4C, SiC particles is (2-7): (5-8): (5-10), and the total mass percentage is 15%-25%;
[0067] A heat dissipation layer 3, the heat dissipation layer 3 covers the surface of the cracking absorption layer 2; the heat dissipation layer 3 comprises graphene, Ag / Cu and silicone resin, and the mass ratio of graphene to Ag / Cu is (5-10):(5-10), and the total mass percentage is 10%-20%;
[0068] A heat insulation layer 4, the heat insulation layer 4 covers the surface of the heat dissipation layer 3; the heat insulation layer 4 comprises ZrO2, Mo, Y2O3 and polysilazane, and the mass ratio of ZrO2, Mo and Y2O3 is (5-10): (3-7): (4-8), and the total mass percentage is 18%-25%;
[0069] A reflective absorbing layer 5, wherein the reflective absorbing layer 5 covers the surface of the thermal insulation layer 4; the reflective absorbing layer 5 comprises Al, ZrO2, Fe3O4, cBN, and silicone resin, and the mass ratio of Al, ZrO2, Fe3O4, and cBN is (5-10):(5-10):(3-5):(3-5), and the total mass percentage is 20%-30%.
[0070] It should be noted that the surfaces of the cracking absorption layer 2, the heat dissipation layer 3, the heat insulation layer 4 and the reflective absorbing layer 5 are flat and smooth, and have relatively few internal structural defects.
[0071] In the embodiment of the present application, the pyrolysis absorption layer is covered on the surface of the substrate by spin coating, and the heat dissipation layer is covered on the surface of the pyrolysis absorption layer, and the heat insulation layer is covered on the surface of the heat dissipation layer, and the reflective wave absorbing layer is covered on the surface of the heat insulation layer. Among them, the reflective wave absorbing layer has the effect of reflecting and absorbing waves, the heat insulation layer has the effect of heat insulation, the heat dissipation layer has the effect of heat conduction and heat equalization, and the pyrolysis absorption layer has the effect of absorbing and consuming laser energy and generating high-temperature ceramics, so that each coating of the substrate can achieve the purpose of reflecting and absorbing waves, heat insulation, heat conduction and heat equalization, and absorbing and consuming energy from top to bottom in sequence;
[0072] Furthermore, the reflective absorbing layer, as a surface layer capable of reflecting laser light, reflects part of the laser light by doping with aluminum powder; after laser irradiation, ZrO2 undergoes a phase change, consuming part of the energy, and at the same time, causing the emissivity of the coating to increase, further reducing the irradiation energy of the laser; nano-cBN compensates for phase defects in the coating, improves the mechanical properties of the reflective absorbing layer, and prolongs the service life of the coating. In addition, the doped Fe3O4 particles can absorb radar waves, allowing the drone to avoid radar tracking to a certain extent.
[0073] The thermal insulation layer is an intermediate coating that can isolate heat transfer. It uses the cracking of polysilazane to absorb part of the laser energy and heat to generate SiCN ceramics with high-temperature thermal insulation. ZrO2, Mo, and Y2O3 particles have the characteristics of low thermal conductivity and high temperature resistance, which prevent heat from being transferred to the inside of the coating.
[0074] As an intermediate layer coating that can quickly conduct heat to avoid heat accumulation, the heat dissipation layer uses the delayed effect of the thermal insulation layer to block heat transfer, and uses the strong thermal conductivity of graphene, Cu or Ag to quickly transfer heat laterally to increase the heated area, thereby avoiding damage to the coating caused by heat accumulation.
[0075] The cracking absorption layer serves as a bottom coating that can absorb and consume heat. It uses polysilazane to absorb laser energy and interacts with SiC to crack and produce a large amount of SiCN ceramics, which consumes the energy inside the coating. At the same time, it cooperates with the high-temperature resistant TiB2 and TiC converted from TiO2 and B4C to hinder the transfer of heat, thereby protecting the drone.
[0076] Therefore, the laser protection multi-layer composite structure applied to UAV is reasonably designed. Through the multi-layer structure with different material ratios, the protective coating of the UAV takes into account the anti-laser performance, mechanical properties, wave absorption performance, and thermal insulation performance.
[0077] In addition, after 3 minutes of laser ablation with a fiber laser at a power of 2 kW, the matrix of the laser protection multilayer composite structure used in UAVs was still not ablated through. The ceramic generation rate of the coating after laser irradiation was as high as 85%, and the hardness reached 700 HV. 0.2 , which can effectively protect the coating.
[0078] According to the second aspect of the present invention, see Figure 2 , provides a method for manufacturing a multi-layer composite structure for laser protection applied to drones, which uses spin coating to prepare multiple layers of coatings with different components to achieve different functions in the field of laser protection for drones. Moreover, it reduces the thermal damage to the drone's thin-walled structure and precision devices during the coating preparation process.
[0079] Specifically, the manufacturing method of the laser protection multilayer composite structure applied to the unmanned aerial vehicle comprises the following steps:
[0080] Step S100, pre-treating the substrate;
[0081] Step S200, preparing a cracking absorption layer, comprising:
[0082] Step S201, preparing a precursor solution; wherein the precursor solution comprises polysilazane and a diluent; the diluent is n-butanol, or acetone, or ethylene dichloride, or ethanol;
[0083] Step S202, adding TiO2, B4C, and SiC particles to the precursor solution in sequence, stirring evenly, placing the mixture in an ultrasonic disperser for ultrasonic dispersion for 5-10 minutes, and then adding a defoamer with a mass fraction of 0.4%-0.8%, and continuing to stir in an electromagnetic stirrer for 10-15 minutes to form a first mixed solution; wherein, in the first mixed solution, the mass ratio of TiO2, B4C, and SiC particles is 2-7:5-8:5-10, and the total mass percentage is 15%-25%;
[0084] Step S203, coating the pretreated substrate with the first mixed solution by spin coating, and curing in an Ar atmosphere to form a cracking absorption layer on the surface of the substrate;
[0085] Step S300, preparing a heat dissipation layer, comprising:
[0086] Step S301, preparing an organic resin mixed solution; wherein the organic resin mixed solution comprises an organic silicon resin and a solvent; the solvent is acetone, ethanol, or xylene;
[0087] Step S302, adding graphene, Cu or Ag particles to the organic resin mixed solution in sequence, stirring evenly, placing it in an ultrasonic disperser for ultrasonic dispersion for 3-5 minutes, and then adding a defoamer with a mass fraction of 0.3%-0.5%, and continuing to stir in an electromagnetic stirrer for 8-10 minutes to form a second mixed solution; wherein, in the second mixed solution, the mass ratio of graphene to Ag / Cu is 5-10:5-10, and the total mass percentage is 10%-20%;
[0088] Step S303, coating the heat dissipation layer with the second mixed solution by spin coating, and curing in an Ar atmosphere to form a heat dissipation layer on the surface of the cracking absorption layer;
[0089] Step S400, preparing a heat insulation layer, includes:
[0090] Step S401, preparing a precursor solution; wherein the precursor solution comprises polysilazane and a diluent; the diluent is n-butanol, or acetone, or ethylene dichloride, or ethanol;
[0091] Step S402, adding ZrO2, Mo, and Y2O3 particles to the precursor solution in sequence, stirring evenly, placing the mixture in an ultrasonic disperser for ultrasonic dispersion for 8-12 minutes, and then adding a defoamer with a mass fraction of 0.4%-0.7%, and continuing to stir in an electromagnetic stirrer for 10-15 minutes to form a third mixed solution; wherein, in the third mixed solution, the mass ratio of ZrO2, Mo, and Y2O3 is 5-10:3-7:4-8, and the total mass percentage is 18%-25%;
[0092] Step S403, coating the heat insulation layer with the third mixed solution by spin coating, and curing in an Ar atmosphere to form a heat insulation layer on the surface of the heat dissipation layer;
[0093] Step S500, preparing a reflective absorbing layer, includes:
[0094] Step S501, preparing an organic resin mixed solution; wherein the organic resin mixed solution comprises an organic silicon resin and a diluent; the diluent is acetone, or ethanol, or ethylene dichloride;
[0095] Step S502, Al, ZrO2, Fe3O4, cBN particles are added to the organic resin mixed solution in sequence, stirred evenly, and then placed in an ultrasonic disperser for ultrasonic dispersion for 8-12 minutes, and then a defoamer with a mass fraction of 0.4%-0.7% is added, and the mixture is stirred in an electromagnetic stirrer for 9-12 minutes to form a fourth mixed solution; wherein, in the fourth mixed solution, the mass ratio of Al, ZrO2, Fe3O4, and cBN is 5-10:5-10:3-5:3-5, and the total mass percentage is 20%-30%;
[0096] Step S503 , coating the reflective absorbing layer with the fourth mixed solution by spin coating, and curing the mixed solution in an Ar atmosphere to form a reflective absorbing layer on the surface of the heat insulation layer.
[0097] In the above embodiment, the cracking absorption layer, the heat dissipation layer, the heat insulation layer, and the reflective absorbing layer. Moreover, in the laser protection multilayer composite structure prepared by the manufacturing method of the laser protection multilayer composite structure applied to unmanned aerial vehicles, the reflective absorbing layer is a surface layer capable of reflecting lasers, and a part of the laser is reflected by doping aluminum powder; after laser irradiation, ZrO2 undergoes a phase change, consuming a part of the energy, and at the same time, causing the emissivity of the coating to increase, further reducing the irradiation energy of the laser; nano cBN compensates for the phase defects in the coating, improves the mechanical properties of the reflective absorbing layer, and prolongs the service life of the coating. In addition, the doped Fe3O4 particles can absorb radar waves, allowing the unmanned aerial vehicle to avoid radar tracking to a certain extent.
[0098] The thermal insulation layer is an intermediate coating that can isolate heat transfer. It uses the cracking of polysilazane to absorb part of the laser energy and heat to generate SiCN ceramics with high-temperature thermal insulation. ZrO2, Mo, and Y2O3 particles have the characteristics of low thermal conductivity and high temperature resistance, which prevent heat from being transferred to the inside of the coating.
[0099] As an intermediate layer coating that can quickly conduct heat to avoid heat accumulation, the heat dissipation layer uses the delayed effect of the thermal insulation layer to block heat transfer, and uses the strong thermal conductivity of graphene, Cu or Ag to quickly transfer heat laterally to increase the heated area, thereby avoiding damage to the coating caused by heat accumulation.
[0100] The cracking absorption layer serves as a bottom coating that can absorb and consume heat. It uses polysilazane to absorb laser energy and interacts with SiC to crack and produce a large amount of SiCN ceramics, which consumes the energy inside the coating. At the same time, it cooperates with the high-temperature resistant TiB2 and TiC converted from TiO2 and B4C to hinder the transfer of heat, thereby protecting the drone.
[0101] Optionally, preparing a precursor solution comprises:
[0102] Dissolve polysilazane in n-butanol, or acetone, or ethylene dichloride, or ethanol to obtain a precursor solution, and stir it with an electric stirrer for 3-6 minutes; wherein the mass fraction of polysilazane in the precursor solution is 55-65%.
[0103] In the above embodiment, the preparation method of the precursor solution is relatively simple, which helps the precursor solution to achieve corresponding technical effects after the cracking absorption layer 2, the heat dissipation layer 3, the thermal insulation layer 4 and the reflective absorbing layer 5 are formed.
[0104] Optionally, preparing an organic resin mixed solution comprises:
[0105] The organic silicon resin is dissolved in acetone, ethanol or dichloroethane to obtain an organic resin mixed solution, and an electric stirrer is used to stir the solution for 2-3 minutes; wherein the mass fraction of the organic silicon resin in the organic resin mixed solution is 50-60%.
[0106] In the above embodiment, the preparation method of the organic resin mixed solution is relatively simple and helps to ensure the uniformity of the organic resin mixed solution.
[0107] Optionally, the substrate is pretreated, including:
[0108] The substrate surface and edges were smoothed with sandpaper and then ultrasonically cleaned in acetone.
[0109] In the above embodiment, it is helpful to prepare the cleavage absorption layer 2 with uniform thickness on the surface of the substrate, and it is also helpful to ensure the bonding strength between the substrate 1 and the cleavage absorption layer 2 to prevent the cleavage absorption layer 2 from falling off the substrate 1.
[0110] Optionally, the material of the substrate is a carbon composite material, which makes the drone have the advantages of light weight, high strength and impact resistance; the sandpaper is 100-mesh sandpaper, which helps to smooth the surface of the substrate; the temperature of ultrasonic cleaning is 25°C and the cleaning time is 5 minutes, which helps to ensure the cleaning effect of the substrate surface.
[0111] Optionally, in step S202, after TiO2, B4C, and SiC particles are sequentially added to the precursor solution, the precursor solution is stirred with an electric stirrer for 5-7 minutes;
[0112] And / or, in step S302, after graphene, Cu or Ag particles are sequentially added to the organic silicone resin mixed solution, the organic resin mixed solution is stirred with an electric stirrer for 3-5 minutes;
[0113] And / or, in step 402, after ZrO2, Mo, and Y2O3 particles are added to the precursor solution in sequence, the precursor solution is stirred with an electric stirrer for 5-7 minutes.
[0114] And / or, in step 502, after Al, ZrO2, Fe3O4, and cBN particles are sequentially added to the organic silicon resin mixed solution, the precursor solution is stirred with an electric stirrer for 3-5 minutes.
[0115] In the above embodiment, the stirring method is relatively reasonable, which helps to ensure the uniformity of the mixed solution.
[0116] Optionally, in step S202, the particle sizes of TiO2, B4C, and SiC particles are 300nm-700nm respectively;
[0117] and / or, in step 302, the particle sizes of graphene, Cu or Ag are 500 nm-1000 nm respectively;
[0118] And / or, in step 402, the particle sizes of ZrO2, Mo, and Y2O3 particles are 500nm-800nm respectively.
[0119] And / or, in step 502, the particle sizes of Al, ZrO2, Fe3O4, and cBN particles are 600nm-1000nm respectively.
[0120] In the above-mentioned embodiment, the particle size of each material is relatively reasonable, which helps to evenly distribute it in the mixed solution.
[0121] Optionally, when the spin coating method is used for coating, the rotation speed is 1600r / min-2000r / min and the time is 30s-60s. This makes the coating method more reasonable and helps to form the cracking absorption layer 2, the heat dissipation layer 3, the heat insulation layer 4 and the reflective absorption layer 5 with uniform thickness.
[0122] Optionally, when curing is performed in an Ar atmosphere, the curing conditions are as follows:
[0123] The temperature was first raised to 230°C at a heating rate of 2°C / min and kept at this temperature for 2h, and then cooled to 25°C at a cooling rate of 5°C / min and kept at this temperature for 0.5h.
[0124] In the above embodiment, the curing effect of the cracking absorption layer 2, the heat dissipation layer 3, the heat insulation layer 4 and the reflective absorbing layer 5 can be ensured.
[0125] Optionally, the thickness of the cracking absorption layer, heat dissipation layer, heat insulation layer, and reflection absorption layer is 200 μm-400 μm. This makes the thickness of the cracking absorption layer, heat dissipation layer, heat insulation layer, and reflection absorption layer reasonably designed, so as to better achieve the purpose of each coating of the substrate from top to bottom to achieve reflection absorption, heat insulation, heat conduction and heat equalization, absorption and consumption of laser energy and generate high-temperature ceramics.
[0126] It is to be understood that the above embodiments are merely exemplary embodiments used to illustrate the principles of the present invention, but the present invention is not limited thereto. For those of ordinary skill in the art, various modifications and improvements can be made without departing from the spirit and essence of the present invention, and these modifications and improvements are also considered to be within the scope of protection of the present invention.
Claims
1. A laser protection multi-layer composite structure applied to unmanned aerial vehicles, characterized in that: include: A cracking absorption layer, the cracking absorption layer covers the surface of the substrate; the cracking absorption layer comprises TiO2, B4C, SiC particles and polysilazane; A heat dissipation layer, the heat dissipation layer covers the surface of the cracking absorption layer; the heat dissipation layer comprises graphene, Ag / Cu and silicone resin; A heat insulation layer, the heat insulation layer covers the surface of the heat dissipation layer; the heat insulation layer comprises ZrO2, Mo, Y2O3 and polysilazane, and the mass ratio of ZrO2, Mo and Y2O3 is 5-10:3-7:4-8, and the total mass percentage is 18%-25%; A reflective absorbing layer is covered on the surface of the thermal insulation layer; the reflective absorbing layer comprises Al, ZrO2, Fe3O4, cBN and silicone resin, and the mass ratio of Al, ZrO2, Fe3O4 and cBN is 5-10:5-10:3-5:3-5, and the total mass percentage is 20%-30%.
2. A method for preparing a laser protection multilayer composite structure for use in unmanned aerial vehicles, characterized in that: The steps include: Step S100, pre-treating the substrate; Step S200, preparing a cracking absorption layer, comprising: Step S201, preparing a precursor solution; wherein the precursor solution comprises polysilazane and a diluent; the diluent is n-butanol, or acetone, or ethylene dichloride, or ethanol; Step S202, adding TiO2, B4C, and SiC particles to the precursor solution in sequence, stirring evenly, placing the mixture in an ultrasonic disperser for ultrasonic dispersion for 5-10 minutes, and then adding a defoamer with a mass fraction of 0.4%-0.8%, and continuing to stir in an electromagnetic stirrer for 10-15 minutes to form a first mixed solution; wherein, in the first mixed solution, the mass ratio of TiO2, B4C, and SiC particles is 2-7:5-8:5-10, and the total mass percentage is 15%-25%; Step S203, coating the pretreated substrate with the first mixed solution by spin coating, and curing in an Ar atmosphere to form a cracking absorption layer on the surface of the substrate; Step S300, preparing a heat dissipation layer, comprising: Step S301, preparing an organic resin mixed solution; wherein the organic resin mixed solution comprises an organic silicon resin and a solvent; the solvent is acetone, ethanol, or xylene; Step S302, adding graphene, Cu or Ag particles to the organic resin mixed solution in sequence, stirring evenly, placing it in an ultrasonic disperser for ultrasonic dispersion for 3-5 minutes, and then adding a defoamer with a mass fraction of 0.3%-0.5%, and continuing to stir in an electromagnetic stirrer for 8-10 minutes to form a second mixed solution; wherein, in the second mixed solution, the mass ratio of graphene to Ag / Cu is 5-10:5-10, and the total mass percentage is 10%-20%; Step S303, coating the heat dissipation layer with the second mixed solution by spin coating, and curing in an Ar atmosphere to form a heat dissipation layer on the surface of the cracking absorption layer; Step S400, preparing a heat insulation layer, includes: Step S401, preparing a precursor solution; wherein the precursor solution comprises polysilazane and a diluent; the diluent is n-butanol, or acetone, or ethylene dichloride, or ethanol; Step S402, adding ZrO2, Mo, and Y2O3 particles to the precursor solution in sequence, stirring evenly, placing the mixture in an ultrasonic disperser for ultrasonic dispersion for 8-12 minutes, and then adding a defoamer with a mass fraction of 0.4%-0.7%, and continuing to stir in an electromagnetic stirrer for 10-15 minutes to form a third mixed solution; wherein, in the third mixed solution, the mass ratio of ZrO2, Mo, and Y2O3 is 5-10:3-7:4-8, and the total mass percentage is 18%-25%; Step S403, coating the heat insulation layer with the third mixed solution by spin coating, and curing in an Ar atmosphere to form a heat insulation layer on the surface of the heat dissipation layer; Step S500, preparing a reflective absorbing layer, includes: Step S501, preparing an organic resin mixed solution; wherein the organic resin mixed solution comprises an organic silicon resin and a diluent; the diluent is acetone, or ethanol, or ethylene dichloride; Step S502, Al, ZrO2, Fe3O4, cBN particles are added to the organic resin mixed solution in sequence, stirred evenly, and then placed in an ultrasonic disperser for ultrasonic dispersion for 8-12 minutes, and then a defoamer with a mass fraction of 0.4%-0.7% is added, and the mixture is stirred in an electromagnetic stirrer for 9-12 minutes to form a fourth mixed solution; wherein, in the fourth mixed solution, the mass ratio of Al, ZrO2, Fe3O4, and cBN is 5-10:5-10:3-5:3-5, and the total mass percentage is 20%-30%; Step S503 , coating the reflective absorbing layer with the fourth mixed solution by spin coating, and curing the mixed solution in an Ar atmosphere to form a reflective absorbing layer on the surface of the heat insulation layer.
3. The method for preparing a laser protection multilayer composite structure for use in unmanned aerial vehicles according to claim 2, characterized in that: Pre-treat the substrate, including: The substrate surface and edges were smoothed with sandpaper and then ultrasonically cleaned in acetone.
4. The method for preparing a laser protection multilayer composite structure for use in unmanned aerial vehicles according to claim 2, characterized in that: Prepare a precursor solution, including: The polysilazane is dissolved in n-butanol, acetone, ethylene dichloride, or ethanol to obtain a precursor solution, and an electric stirrer is used for stirring for 3-6 minutes; wherein the mass fraction of the polysilazane in the precursor solution is 55-65%.
5. The method for preparing a laser protection multilayer composite structure for use in unmanned aerial vehicles according to claim 2, characterized in that: An organic resin mixed solution is prepared, comprising: The organic silicon resin is dissolved in acetone, ethanol or dichloroethane to obtain an organic resin mixed solution, and an electric stirrer is used to stir the solution for 2-3 minutes; wherein the mass fraction of the organic silicon resin in the organic resin mixed solution is 50-60%.
6. The method for preparing a laser protection multilayer composite structure for use in unmanned aerial vehicles according to claim 3, characterized in that: The material of the substrate is a carbon composite material; the sandpaper is 100-mesh sandpaper; the temperature of ultrasonic cleaning is 25° C., and the cleaning time is 5 minutes.
7. The method for preparing a laser protection multilayer composite structure for use in unmanned aerial vehicles according to claim 2, characterized in that: In step S202, after TiO2, B4C, and SiC particles are sequentially added to the precursor solution, the precursor solution is stirred with an electric stirrer for 5-7 minutes; And / or, in step 402, after ZrO2, Mo, and Y2O3 particles are added to the precursor solution in sequence, the precursor solution is stirred with an electric stirrer for 5-7 minutes.
8. The method for preparing a laser protection multilayer composite structure for use in unmanned aerial vehicles according to claim 2, characterized in that: In step S302, after graphene, Cu or Ag particles are sequentially added to the organic silicone resin mixed solution, the organic resin mixed solution is stirred with an electric stirrer for 3-5 minutes; And / or, in step 502, after Al, ZrO2, Fe3O4, and cBN particles are sequentially added to the organic silicon resin mixed solution, the precursor solution is stirred with an electric stirrer for 3-5 minutes.
9. The method for preparing a laser protection multilayer composite structure for use in unmanned aerial vehicles according to claim 2, characterized in that: In step S202, the particle sizes of TiO2, B4C, and SiC particles are 300nm-700nm respectively; and / or, in step 302, the particle sizes of graphene, Cu or Ag are 500 nm-1000 nm respectively; and / or, in step 402, the particle sizes of ZrO2, Mo, and Y2O3 particles are 500nm-800nm respectively; And / or, in step 502, the particle sizes of Al, ZrO2, Fe3O4, and cBN particles are 600nm-1000nm respectively.
10. The method for preparing a laser protection multilayer composite structure for use in unmanned aerial vehicles according to claim 2, characterized in that: When the coating is performed by spin coating, the rotation speed is 1600 r / min-2000 r / min, and the time is 30 s-60 s.
11. The method for preparing a laser protection multilayer composite structure for use in unmanned aerial vehicles according to claim 2, characterized in that: When curing is carried out in an Ar atmosphere, the curing conditions are as follows: The temperature was first raised to 230°C at a heating rate of 2°C / min and kept at this temperature for 2h, and then cooled to 25°C at a cooling rate of 5°C / min and kept at this temperature for 0.5h.
12. The method for preparing a laser protection multilayer composite structure for use in unmanned aerial vehicles according to claim 2, characterized in that: The thickness of the cracking absorption layer, the heat dissipation layer, the heat insulation layer and the reflection absorption layer are all 200 μm-400 μm.
Citation Information
Patent Citations
Laser protection coating and manufacturing method thereof
CN109536870A
Laser protection coating and preparation method thereof
CN111996531A
Laser-ablation-resistant coating for surface of base material and preparation method
CN112779535A